Abnormal Striatal-Cortical Networks Contribute to the Attention/Executive Function Deficits in Idiopathic REM Sleep Behavior Disorder: A Resting State Functional MRI Study - Zhang, Hong-Ju; Wang, Sheng-Hui; Bai, Ying-Ying; Zhang, Jie-Wen; Chen, Shuai (Frontiers in Aging Neuroscience, 2021)
Introduction: The structural and functional damages of the striatum were evident in idiopathic REM sleep behavior disorder (iRBD). With the increase in research on iRBD, cognitive impairment in iRBD is receiving more attention. However, the mechanism of cognitive impairment in idiopathic RBD (iRBD) was poorly understood. Methods: Neuropsychological assessment were carried out in 21 polysomnographies(PSGs) confirmed iRBD patients and 22 normal controls. Both the regional homogeneity (ReHo) and seed-based functional connectivity (FC) rs-fMRI analyses were applied to explore the FC abnormalities and their association with cognition in patients with iRBD. Positive ReHo clusters were set as seeds for further FC analysis. Results: iRBD patients presented cognitive deficits in attention/working memory, executive function, immediate memory, and visuospatial ability. ReHo analysis revealed abnormal spontaneous brain activity in the striatum (right caudate, left pallidum and bilateral putamen) in patients with iRBD. FC analysis showed decreased striatum-related FCs in the frontal, temporal, occipital lobes, thalamus, and anterior cingulate gyrus, as well as decreased intrinsic FCs between bilateral putamen and between caudate and pallidum. Deficits in attention/working memory, executive function, and immediate memory were associated with abnormal striatal-cortical FCs including the frontal, temporal, and anterior cingulate cortices. Conclusions: In conclusion, functional changes in the striatum and cognitive impairment in iRBD were once again confirmed in the present study. The impairment of attention/executive function in iRBD was associated with the striatal-cortical network, especially the striatal-frontal network. These findings support the role of the striatum not only in motor function but also in cognitive impairment in iRBD.